Facile, Versatile and Stepwise Synthesis of High‐Performance Oligomer Acceptors for Stable Organic Solar Cells - Zhang, Chen; Song, Jiali; Xue, Jingwei; Wang, Shijie; Ge, Zhongwei; Man, Yuheng; Ma, Wei; Sun, Yanming (Angewandte Chemie International Edition, 2023)
Oligomer acceptors have recently emerged as promising photovoltaic materials for achieving high power conversion efficiency (PCE) and long‐term stability in organic solar cells (OSCs). However, the limited availability of diverse acceptors, resulting from the sole synthetic approach, has hindered their potential for future industrialization. In this study, we present a facile and effective stepwise approach that utilizes two consecutive Stille coupling reactions for the synthesis of oligomer acceptors. To demonstrate the feasibility of the novel approach, we successfully synthesize a trimer acceptor, Tri‐Y6‐OD, and further systematically investigate the impact of oligomerization on device performance and stability. The results reveal that this approach has significant advantages compared to the conventional method, including reduced formation of unwanted by‐products and lower difficulties in purification. Remarkably, the OSC based on PM6 : Tri‐Y6‐OD achieves an impressive PCE of 18.03 % and maintains 80 % of the initial PCE (T80) for 1523 h under illumination, surpassing the performance of the corresponding small molecule acceptor Y6‐OD‐based device. Furthermore, the versatility of the synthetic strategy in obtaining diverse acceptors is further demonstrated. Overall, our findings provide a facile, versatile and stepwise way for synthesizing oligomer acceptors, thereby facilitating the development of stable and efficient OSCs. The stepwise method proposed to synthesize non‐fullerene oligomer acceptors via consecutive Stille coupling reactions offers significant advantages compared to the traditional approach, resulting in fewer unwanted by‐products and easier purification processes. By utilizing this method, the obtained Tri‐Y6‐OD‐based organic solar cells achieved a high power conversion efficiency of 18.03 %, along with excellent stability.